External Debt, Public Investment, and Growth in Low-Income Countries - Nguyen, Toan.; Bhattacharya, Rina.; Clements, Benedict (Washington, D.C. : International Monetary Fund, 2003)
This paper examines the channels through which external debt affects growth in low-income countries. Our results suggest that the substantial reduction in the stock of external debt projected for highly indebted poor countries (HIPCs) would directly increase per capita income growth by about 1 percentage point per annum. Reductions in external debt service could also provide an indirect boost to growth through their effects on public investment. If half of all debt-service relief were channeled for such purposes without increasing the budget deficit, then growth could accelerate in some HIPCs by an additional 0.5 percentage point per annum.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet